A cell-based MAPK reporter assay reveals synergistic MAPK pathway activity suppression by MAPK inhibitor combination in BRAF-driven pediatric low-grade glioma cells - Usta, Diren; Sigaud, Romain; Buhl, Juliane; Selt, Florian; Marquardt, Viktoria; Pauck, David; Jansen, Jennifer; Pusch, Stefan; Ecker, Jonas; Hielscher, Thomas; Vollmer, Johanna; Sommerkamp, Alexander C.; et al. (Molecular cancer therapeutics, 2020)
Pilocytic astrocytomas (PAs) as well as other pediatric low-grade gliomas (pLGGs) exhibit genetic events leading to aberrant activation of the MAPK pathway. The most common alterations are KIAA1549:BRAF fusions, BRAFV600E and NF1 mutations. Novel drugs targeting the MAPK pathway (MAPKi) are prime candidates for the treatment of these single-pathway diseases. We aimed to develop an assay suitable for pre-clinical testing of MAPKi in pLGGs with the goal to identify novel MAPK pathway suppressing synergistic drug combinations. A reporter plasmid (pDIPZ) with a MAPK-responsive ELK-1-binding element driving the expression of destabilized firefly luciferase was generated and packaged using a lentiviral vector system. Pediatric glioma cell lines with a BRAF fusion (DKFZ-BT66) and a BRAFV600E mutation (BT-40) background, respectively, were stably transfected. Modulation of the MAPK pathway activity by MAPKi was measured using the luciferase reporter and validated by detection of phosphorylated protein levels. A screen of a MAPKi library was performed and synergy of selected combinations was calculated. Screening of a MAPKi library revealed MEK inhibitors as the class inhibiting the pathway with the lowest IC50s, followed by ERK and next-generation RAF inhibitors. Combination treatments with different MAPKi classes showed synergistic effects in BRAF fusion as well as BRAFV600E mutation backgrounds. We here report a novel reporter assay for medium- to high-throughput pre-clinical drug testing in pLGG cell lines. The assay confirmed MEK, ERK and next-generation RAF inhibitors as potential treatment approaches for KIAA1549:BRAF and BRAFV600E mutated pLGGs. In addition, the assay revealed that combination treatments synergistically suppressed MAPK pathway activity.